Impact of Dutch in Bengal on Decline of Local Mughal Administration: Exploring the Impact of Dutch Trade and Politics on Bengal's Economy and Politics (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Dutch were in the front in maritime trade in the 17th and early part of the 18th century. De Verenigde Oostindische Compagnie (VOC) or commonly known as the Dutch East India Company dominated the trade in Asian waters in the early modern time. The company created expansive network around the world, Asia in more particular. It is regarded as one of the earliest and largest joint-stock companies in the early modern time. The Dutch East India Company was officially founded and ratified by States General of the Dutch Republic on March 20, 1602 CE. Initially the Company was given 21 years time to trade from the Dutch Republic to the east of Cape of Good Hope and through the Strait of Magellan.[1] After its foundation the Company began to expand its trading network rapidly, first in South East Asia and then in South Asia and Japan. In this article we will make an attempt to shed some light on the Dutch activities in Bengal, their trading activities and their involvement in the geopolitics of Bengal. We will investigate the ramification of the Dutch trading and political activities in Bengal economy and politics.